Case Report: Passive Handstand Promotes Cerebrovascular Elasticity Training and Helps Delay the Signs of Aging: A 40-Year Follow-Up Investigation - Liu, Haonan; Xu, Qian; Xiang, Xin; Liu, Danan; Si, Shengyong; Wang, Lan; Lv, Ying; Liao, Yidong; Yang, Hua (Frontiers in Medicine, 2022)
Background: There are no long-term (>10 years) follow-up evaluations of the effects of handstand exercise or studies on the use of equipment for passive handstand exercise. Objective: To report a 40-year follow-up investigation of a Chinese man who has been practicing passive handstand for 40 years. Design: This observational investigation was conducted in Guizhou Province, China. Participant: A (currently) 66-year-old Chinese man who had been practicing passive handstand exercise for 40 years was followed up. Interventions: Physical and auxiliary examinations were carried out to determine the effects of long-term passive handstand exercise on the human body. Main measures: The participant’s cerebrovascular, spinal health, mental health, and visual acuity as well as the presence of facial aging were examined. Key Results: His cerebral vessels were healthy, he appeared younger than his peers, his cervical spondylosis improved, and his mental state and cognitive function were good. Conclusion: Long-term passive handstand exercise can promote cerebrovascular elasticity training and delay signs of aging. We recommend promoting this passive handstand exercise to the public.